HISTOLOGICAL DESCRIPTION OF THE HAIR FOLLICLE IN THE YOUNG ALPACA - Badajoz L., Elmer (2009)
The present study was carried out to characterize the distribution and an association of hair follicles of alpaca skin. Samples were collected from 42 young Suri and Huacaya alpacas, of both sexes and with various hair colours. Samples were collected by punch skin biopsy in the middle costal zone and processed for histological study using H-E staining. Hair follicles formed follicular nests distributed as a compound follicle group (CFG) and simple follicle group (SFG). The first was composed of primary follicles surrounded by secondary follicles, while that latter was only composed of secondary follicles. Furthermore, primary follicles can be solitary and named Extra Primary Follicle Follicular Group (EPFFG) or forming compound follicle groups named Internal Primary Follicle Follicular Group (IPFFG). Follicular groups are formed by one or more primary follicles and a variable number of secondary follicles; however, in the Suri alpaca, was observed groups of three primary follicles, one larger and central and two smaller at each side. The characteristics of association and distribution of follicles and the cytoarchitecture allowed pointing out the presence of a Hair Follicular Complex in the alpaca skin.